Écriture auto-ethnographique et positionnement: réflexivité entourant l’arabité et le queer - Bouqentar, Lamiae (Alterstice, 2021)
Cet article est un texte réflexif sur mon recours à une écriture auto-ethnographique dans ma recherche doctorale à propos de la migration arabe queer. En tant que chercheure arabe queer migrante, je puise dans la notion de positionnement, qui permet de considérer les expériences des groupes minorisés et racialisés comme une source pertinente de savoir. Inspirée de la tradition auto-ethnographique, je procède en incluant des fragments de récit de soi tirés de mes propres échanges de la vie, pour ainsi problématiser les identifications arabe et queer composant mon positionnement.
Keywords: 2000 à aujourd'hui; 2020-2029; LGBTQIA2+; afrique; amériques; approches et analyses; arts; autoethnographie; canada; communication; cours; discipline; féminisme décolonial; histoire et politique; intersectionnalité; maroc; montréal; premier cycle; périodes historiques; queer; québec; rabat; régions géographiques; sex2283; thématiques; études culturelles; études littéraires

Postcolonial / Décolonial: la preuve par l'art - Toussaint, Evelyne (Presses universitaires du Midi, 2021)
Les liens entre art contemporain, histoire coloniale, postcolonialisme et mouvements décoloniaux sont anciens et multiples. Des artistes, en Occident et ailleurs, depuis plusieurs décennies déjà, revisitent opportunément des concepts que les études postcoloniales ont approfondis ou inventés - agency (agentivité), mimicry (mimétisme/simulacre) ou essentialisme stratégique -, en autant d'outils utiles à démêler la complexité des relations coloniales et, au-delà, de toutes les relations de domination. Des auteurs, relevant de ces champs d'études conservant aujourd'hui toute leur actualité politique, théorique et polémique, disent en retour tout l'intérêt qu'ils portent à la création contemporaine. Associant vingt historiens de l'art et chercheurs en littérature, philosophie, droit ou psychanalyse, Postcolonial/Décolonial. La preuve par l'art réunit des textes portant sur des productions artistiques (Betye Saar, Fred Wilson, Sarkis, Lidwien van de Ven, Voluspa Jarpa, Iris Kensmil, Jean Renoir et bien d'autres), des propositions institutionnelles (Centro de Arte y Comunicación de Buenos Aires, Biennale de Venise ou Van Abbemuseum d'Eindhoven), l'historiographie de l'histoire de l'art ou celle du droit. Une place particulière est réservée aux singularités artistiques, théoriques et juridiques en Amérique latine, lieu d'émergence des théories décoloniales–Page 4 de la couverture.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; cours; discipline; droit; féminisme décolonial; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; science politique et droit; sciences de la gestion; thématiques; économie

Afropea: utopie post-occidentale et post-raciste - Miano, Léonora (Bernard Grasset, 2020)
Léonora Miano n'est pas une Afropéenne (afro-européenne). Ceux qui se définissent ainsi ont grandi en Europe.Marquée par l'Afrique subsaharienne, la sensibilité de l'auteur se distingue de celle des Afropéens. Ceux-ci se sont construits en situation de minorité. Ce qui détermine la perception de soi, complique l'identification et la solidarité entre Afropéens et Subsahariens.La France identifie à l'Afrique tous ses citoyens d'ascendance subsaharienne, privilégiant les natifs de ce continent. Cela ne favorise pas l'ancrage des Afropéens dans leur pays, leur capacité à se sentir responsables de son destin.Pourtant, ceux qui se sont donné un nom - Afropéens - dans lequel Afrique et Europe fusionnent, s'ils sont fidèles aux implications de cette association plus qu'à leur amertume, peuvent incarner un projet de société fraternel, anti-impérialiste et anti-raciste. Dans une France en proie aux crispations identitaires, la perspective afropéenne apparaît encore comme une utopie. De part et d'autre, la tentation du rejet est puissante.
Section: 222 pages ; 21 cm
Keywords: afrique; afrique subsaharienne; afro-féminisme; antiracisme; approches et analyses; arts; com5170; cours; discipline; europe; france; féminisme afropéen; féminisme décolonial; histoire et politique; premier cycle; régions géographiques; thématiques; utopie; études littéraires

Archi-féministes!: art contemporain, théories féministes - Charron, Marie-Ève; Lafortune, Marie-Josée; St-Gelais, Thérèse; Optica (Galerie) (OPTICA, centre d'art contemporain, 2019)
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; femmes* artistes; féminisme décolonial; har4600; histoire de l'art; histoire et politique; montréal; premier cycle; queer; québec; régions géographiques; thématiques; études culturelles

Décolonisons les arts! - Cukierman, Leïla; Dambuy, Gerty; Vergès, Françoise (L'Arche, 2018)
"À l'initiative du collectif "Décoloniser les arts", Leila Cukierman, Gerty Dambury et Françoise Vergès analysent, avec quinze artistes, la colonialité à l'œuvre dans le monde des arts et de la culture en France et proposent des pistes pour une décolonisation des formations, des institutions et des contenus. Décolonisons les arts!, vaste et passionnant objectif, est abordé à partir de pratiques et de textes critiques qui étudient l'absence de formes de narrations prenant à rebours le récit national. L'ouvrage est une invitation à ouvrir le regard et à prêter l'oreille à la transversalité des récits, un appel à se rassembler pour transformer le champ culturel et artistique où la décolonisation vise à l'émancipation créatrice et à une nécessaire et urgente transformation du monde."–Page 4 de la couverture.
Keywords: approches et analyses; arts; cours; critique institutionelle; discipline; europe; france; féminisme décolonial; har4600; histoire de l'art; histoire et politique; premier cycle; régions géographiques; thématiques

Desire change: contemporary feminist art in Canada - Davis, Heather M. (Heather Margaret); Mentoring Artists for Women's Art (McGill-Queen's University Press, 2017)
"In the resistance to the violence of gender-based oppression, vibrant - but often ignored - worlds have emerged, full of nuance, humour, and beauty. Correcting a glaring omission of writing about contemporary feminist work by Canadian artists, Desire Change considers the resurgence of feminist art, thought, and practice in the past decade by examining artworks that respond to themes of diversity and desire. Essays by historians, artists, and curators present an overview of a range of artistic practices including performance, installation, video, textiles, and photography. Contributors address the desire for change through three central frames: how feminist art has significantly contributed to the complex understanding of gender as it intersects with sexuality and race; the necessary critique of patriarchy and institutions as they relate to colonization within the Canadian national-state; and the ways in which contemporary critiques are formed and expressed. The resulting collection addresses art through an activist lens to examine intersectional feminism, decolonization, and feminist institution building in a Canadian context. Heavily illustrated with representative works, Desire Change raises both the stakes and the concerns of contemporary feminist art, with an understanding that feminism is always and necessarily plural."– Provided by publisher.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; cours; discipline; femmes* artistes; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; patriarcat; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Comment être artiste, femme et autochtone au Canada ? Du stigmate à son renversement dans l'art contemporain - Goyon, Marie (Sociologie de l'Art, 2011)
Résumé Cet article analyse les usages de savoir-faire genrés dans la création contemporaine autochtone canadienne. Ils sont considérés dans leur caractère doublement situé, culturel et sexué. Comment analyser les usages des savoir-faire dits « féminins » (couture, broderie) dans les œuvres de plasticiennes contemporaines ? La réflexion s’appuie sur l’étude des trajectoires biographiques et des œuvres de trois artistes canadiennes autochtones. Une double stigmatisation de ces artistes, marquée de stéréotypes ethniques et genrés, est repérée dans les conditions d’exposition de leurs œuvres en tant qu’autochtones (musées d’ethnologie) et en tant que femmes (musées locaux, statut non professionnel des créatrices). Leurs démarches pourront être qualifiées de postcoloniales, interrogeant les frontières normatives entre arts « majeurs » et arts « mineurs », ainsi que la place des arts « premiers » et des femmes créatrices dans l’histoire de l’art
Number: 3
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; art contemporain; art textile; artisanat; artistes autochtones; arts; arts textiles; canada; cours; discipline; femmes* artistes; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; pol4105; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; travaux d'aiguilles

Indigenous women and feminism: politics, activism, culture - Suzack, Cheryl; Huhndorf, Shari M.; Perreault, Jeanne; Barman, Jean (UBC Press, 2010)
"Can the specific concerns of Indigenous women be addressed within current mainstream feminist and post-colonial discussions? Indigenous Women and Feminism: Politics, Activism, Culture proposes that a dynamic new line of inquiry – Indigenous feminism – is necessary to truly engage with the crucial issues of cultural identity, nationalism, and decolonization particular to Indigenous contexts. Through the lenses of politics, activism, and culture, this wide-ranging collection examines the historical roles of Indigenous women, their intellectual and activist work, and the relevance of contemporary literature, art, and performance for an emerging Indigenous feminist project. The questions at the heart of these essays – What is at stake in conceptualizing Indigenous feminism? How does feminism relate to Indigenous claims to land and sovereignty? What lessons can we learn from the past? How do Indigenous women engage ongoing violence and social and political marginalization? – cross disciplinary, national, academic, and activist boundaries to explore in depth the unique political and social positions of Indigenous women."–Page 4 de la couverture."A vital and sophisticated discussion that will change the way we think about modern feminism, Indigenous Women and Feminism will be invaluable to scholars, activists, artists, community organizers, and those concerned with Indigenous and feminist issues at home and abroad."– Résumé de l'éditeur.
Le texte de Tsosie, Rebecca (2011). Native Women and Leadership: An Ethics of Culture and Relationship a été donné en lecture au cours POL4105.
Keywords: activisme; approches et analyses; arts; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; militance; pol4105; premier cycle; premières nations; système colonial; systèmes d'oppressions; territoire; thématiques; études autochtones; études féministes; études littéraires

Les subalternes peuvent-elles parler? - Spivak, Gayatri Chakravorty..; Vidal, Jérôme.. (Éd. Amsterdam, 2009)
Dans le cadre d'un dialogue critique avec Michel Foucault, Gilles Deleuze et la tradition marxiste, G.C. Spivak articule le concept de subalterne (à ne pas confondre avec les notions de minoritaire ou d'opprimé) et s'interroge sur les femmes subalternes du tiers-monde, l'unification des subalternes au sein d'une communauté.
Keywords: approches et analyses; arts; care; com5170; corps; cours; discipline; féminisme décolonial; har4600; histoire et politique; incontournable; oui; premier cycle; thématiques; études littéraires; études postcoloniales

Post-colonial studies: The key concepts - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 2000)
This volume provides an essential key to understanding the issues which characterise post-colonialism, explaining what it is, where it is encountered and why it is crucial in forging new cultural identities. As a subject, post-colonial studies stands at the intersection of debates about race, colonialism, gender, politics and language. In the language of post-colonial studies, some words are new, others are familiar words charged with new significance.
https://doi-org.proxy.bibliotheques.uqam.ca/10.4324/9780203449974
Keywords: approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; intersectionnalité; littérature; premier cycle; ressource en ligne; thématiques; études culturelles; études littéraires

With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Section: VIII-268 p. : illustrations ; 26 cm
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Colonialism/postcolonialism - Loomba, Ania (Routledge, 1998)
Colonialism/Postcolonialism est un guide complet mais accessible sur les dimensions historiques, théoriques et politiques des études coloniales et postcoloniales. Ania Loomba examines the key features of the ideologies and history of colonialism, and the relationship of colonial discourse to literature. She goes on to consider the challenges to colonialism, surveying anti-colonial discourses, and recent developments in postcolonial theories and histories. Looking at how sexuality is figured in the texts of colonialism, Colonialism/Postcolonialism shows how contemporary feminist ideas and concepts intersect with those of postcolonialist thought
https://ebookcentral.proquest.com/lib/uqam/detail.action?docID=168653
Keywords: approches et analyses; arts; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; ressource en ligne; thématiques; études littéraires

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Minnesota University Press, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Contenu: Introduction / Aamir Mufti and Ella Shohat – pt. I. Contesting Nations. 1. Zionism from the Standpoint of Its Victims / Edward W. Said. 2. Sephardim in Israel: Zionism from the Standpoint of Its Jewish Victims / Ella Shohat. 3. Of Balkans and Bantustans: Ethnic Cleansing and the Crisis in National Legitimation / Rob Nixon. 4. "No Longer in a Future Heaven": Gender, Race, and Nationalism / Anne McClintock. 5. Currying Favor: The Politics of British Educational and Cultural Policy in India, 1813-54 / Gauri Viswanathan. 6. The Nation as Imagined Community / Jean Franco – pt. II. Multiculturalism and Diasporic Identities. 7. On the Question of a Theory of (Third) World Literature / Madhava Prasad. 8. Caliban Speaks Five Hundred Years Later / Roberto Fernandez Retamar. 9. The Local and the Global: Globalization and Ethnicity / Stuart Hall. 10. Multiculturalism and the Neoconservatives / Robert Stam. 11. Shuckin' Off the African-American Native Other: What's "Po-Mo" Got to Do with It? / Wahneema Lubiano. 12. Identity, Meaning, and the African-American / Michael Hanchard. 13. Just Looking for Trouble: Robert Mapplethorpe and Fantasies of Race / Kobena Mercer – pt. III. Gender and the Politics of Race. 14. Under Western Eyes: Feminist Scholarship and Colonial Discourses / Chandra Talpade Mohanty. 15. Traddutora, Traditora: A Paradigmatic Figure of Chicana Feminism / Norma Alarcon. 16. American Indian Women: At the Center of Indigenous Resistance in Contemporary North America / M. Annette Jaimes and Theresa Halsey. 17. "On the Threshold of Woman's Era": Lynching, Empire, and Sexuality in Black Feminist Theory / Hazel V. Carby. 18. Making Empire Respectable: The Politics of Race and Sexual Morality in Twentieth-Century Colonial Cultures / Ann Laura Stoler. 19. Age, Race, Class, and Sex: Women Redefining Difference / Audre Lorde. 20. Gender Is Burning: Questions of Appropriation and Subversion / Judith Butler. 21. Sisterhood: Political Solidarity between Women / Bell Hooks – pt. IV. Postcolonial Theory. 22. Not You/Like You: Postcolonial Women and the Interlocking Questions of Identity and Difference / Trinh T. Minh-ha. 23. Is the "Post-" in "Postcolonial" the "Post-" in "Postmodern"? / Kwame Anthony Appiah. 24. The World and the Home / Homi K. Bhabha. 25. Reading Africa through Foucault: V.Y. Mudimbe's Reaffirmation of the Subject / Manthia Diawara. 26. Teaching for the Times / Gayatri Chakravorty Spivak. 27. Postcolonial Criticism and Indian Historiography / Gyan Prakash. 28. The Postcolonial Aura: Third World Criticism in the Age of Global Capitalism / Arif Dirlik. Le texte "Age, Race, Class, and Sex : Women Redefining Difference" de Audre Lorde a été donné en lecture au cours LIT4700.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

The post-colonial studies reader - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 1995)
The Post-Colonial Studies Reader is the most comprehensive selection of key texts in post-colonial theory and criticism yet compiled. This collection covers a huge range of topics, featuring nearly ninety of the discipline's most widely read works. The Reader's 90 extracts are designed to introduce the major issues and debates in the field of post-colonial literary studies. This field itself, however, has become so varied that no collection of readings could encompass every voice which is now giving itself the name "post-colonial." The editors, in order to avoid a volume which is simply a critical canon, have selected works representing arguments with which they do not necessarily agree, but rather which above all stimulate discussion, thought and further exploration. Post-colonial "theory" has occurred in all societies into which the imperial force of Europe has intruded, though not always in the official form of theoretical text. Like the description of any other field the term has come to mean many things, but this volume hinges on one incontestable phenomenon: the "historical fact"of colonialism, and the palpable consequences to which this phenomenon gave rise. The topic involves talk about experience of various kinds: migration, slavery, suppression, resistance, representation, difference, race, gender, place, and reaction to the European influence, and about the fundamental experiences of speaking and writing by which all these come into being. In compiling this reader, the editors have sought to stimulate people to ask: "How might a genuinely post-colonial literary enterprise proceed?" The fourteen sections include: Issues and Debates; Universality and Difference; Textual Representation and Resistance; Postmodernism and Post-Colonialism; Nationalism; Hybridity; Ethnicity and Indigenity; Feminism and Post-Colonialism; Language; The Body and Performance; History; Place; Education; and Production and Consumption. Contributors include many of the leading post-colonial theorists and critics–such as Franz Fanon, Chinua Achebe, Gayatri Chakravorty Spivak, Ngugi wa Thiong'o, Homi Bhabba, Derek Walcott, Edward Said, and Trinh T. Minh-ha–in addition to a number of the discourse's newer voices. The Post-Colonial Studies Reader will prove an authoritative compilation, representing an invaluable contribution to the study of post-colonial theory and criticism.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; périodes historiques; thématiques; études culturelles; études littéraires